Effects of the Intramode-Group Coupling Induced by the Elliptical Deformation of Orbital Angular Momentum Fibers - Hu Zhang (IEEE, 2022)
Based on the coupling mode theory and numerical simulation, intramode-group coupling in orbital angular momentum (OAM) fibers with elliptical deformation is analyzed in depth. The elliptical deformation not only introduces a time delay difference between even and odd modes of the same high-order vector mode but also destroys the structure of the high-order vector modes; the structural damage depends on the strength of the elliptical deformation. When the elliptical deformation is relatively small, the structural damage of high-order vector modes can be ignored and coupling can be thought as occurring only between two OAM modes composed of the same high-order vector mode. While the elliptical deformation becomes larger, the structural damage cannot be ignored, coupling appears among four OAM modes in the same OAM mode group, and the coupling between two OAM modes composed of the same high-order vector mode is more serious. The results will pave the way for the establishment of accurate propagation models and the optimization of the OAM fiber design.